The smart climate observation network that covers all Africa - Selker, John; Giesen, Nick van de; Annor, Frank (Technical Centre for Agricultural and Rural Cooperation, 2018)
There is a lack of weather and climate observation stations in Africa, while food production, harvest predictions, and disaster mitigation would benefit from improved data-accessible observation. A new smart and sustainable weather and climate observation network now addresses the important challenge of monitoring the weather in the continent.